2015
DOI: 10.1002/path.4545
|View full text |Cite
|
Sign up to set email alerts
|

High nitric oxide production, secondary to inducible nitric oxide synthase expression, is essential for regulation of the tumour‐initiating properties of colon cancer stem cells

Abstract: Chronic inflammation is a leading cause of neoplastic transformation in many human cancers and especially in colon cancer (CC), in part due to tumour promotion by nitric oxide (NO) generated at inflammatory sites. It has also been suggested that high NO synthesis, secondary to inducible NO synthase (iNOS) expression, is a distinctive feature of cancer stem cells (CSCs), a small subset of tumour cells with self-renewal capacity. In this study we explored the contribution of NO to the development of colon CSC fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Elevated NO synthase 2 (NOS2) expression correlates with decreased survival in human glioma patients [46]. Previously, we and others have demonstrated that NOS2 inhibition slowed colon and glioma stem cells growth in vivo animal models [47, 46]. Accordingly, we report that targeting Hes1 downregulates NOS2, IL1B, IL6 and NF-κB2 mRNA levels.…”
Section: Discussionmentioning
confidence: 89%
“…Elevated NO synthase 2 (NOS2) expression correlates with decreased survival in human glioma patients [46]. Previously, we and others have demonstrated that NOS2 inhibition slowed colon and glioma stem cells growth in vivo animal models [47, 46]. Accordingly, we report that targeting Hes1 downregulates NOS2, IL1B, IL6 and NF-κB2 mRNA levels.…”
Section: Discussionmentioning
confidence: 89%
“…Another important oncogenic pathway in cancer promoted by NO to induce proliferation and migration is the Wnt/β-catenin pathway, as suggested by the activation of Wnt target genes following the overexpression of iNOS in cultured human colon and breast cancer cells (Du et al, 2013). Interestingly, NO can also support tumor-forming cancer stem cells (CSCs), as NO produced in cultured human colon CSCs was found to drive stemness-related signaling pathways, central to colon tumor initiation and progression (Puglisi et al, 2015). In contrast to the role that NO plays in supporting oncogenic pathways in cancer, NO also exhibits an anti-proliferative role by suppressing oncogenic pathways or by activating tumor-suppressing ones.…”
Section: Dichotomous Roles Of No In Cancermentioning
confidence: 99%
“…NOS2 expression in these patients greatly increases their risk of developing colon cancer [24]. Additionally, colorectal cancer stem cells are dependent on NO synthesis and NOS expression for tumor initiation [25]. However, early stage colon cancer patients have been shown to have low NOS2 in their colonic epithelium.…”
Section: No: Modulator Of the Tmementioning
confidence: 99%